On Moral Values in Higher Education: A Critical Survey of Research in English in the Last Twenty-Five Years - الخوالدة سميرة (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2021)
This study aims to survey the presence and efficacy of moral values and ethical standards in higher education through examining selected literature written by specialists on the subject in the last twenty-five years, covering books, websites, and articles in academic journals. The survey involves analyzing about a hundred publications written in English, and identifying them under one of several categories, including: “theory, history and philosophy of morals and ethics in higher education programs”; “calls for synthesizing moral values and professional ethics in higher education”; and “the role of faculty and non-teaching staff in the development of students’ moral sense.” A considerable number of applied research studies are also found, dealing with proposed models and actual experiments in this area. The findings of the present study indicate that the general tendency among the authors surveyed is to demand the merging of moral development, one way or another, into university curricula, as a means to better prepare students to assume positive and effective roles in the service of humanity in general and of their own societies in particular. The study holds that such demands are likely motivated by the recent economic crises and the belief that it was caused by morally bankrupt business leaders who did not receive adequate university training in ethics.